A Correlation Study between the Theme of Egyptian Novel "Zaynab" and Malaysian Novel "Faridah Hanom" - Rosni Samah; Normazla Ahmad Mahir (Center For Promoting Ideas, USA, 2024)
International Journal of Humanities and Social Science Vol. 3 No. 12 [Special Issue –June 2013]